Sus scrofa Linnaeus 1758 - Wilson, Don E.; Mittermeier, Russell A. (Zenodo, 2011)
16. Eurasian Wild PigSus scrofa French: Sanglier d’'Eurasie / German: Wildschwein / Spanish: Jabali Other common names: Wild Boar; Indochinese Pig (bucculentus), Indonesian Banded Pig (vittatus) Taxonomy. Sus scrofa Linnaeus, 1758, Germany. S. scrofa is the most widespread species of naturally occurring wild pig. Many of the more distinctive regional forms of these animals were originally described as full species, e.g. villatus, cristatus, leucomystax, moupinensis, and meridionalis, respectively from Sumatra, India, Japan, China, and Sardinia. Later and more comprehensive taxonomic reviews have combined many of these taxa into one species, mostly on the recognition that the different forms of S. scrofa formed a stepped cline extending from Western Europe to the Far East and insular South-east Asia. This gradual change in morphological characteristics allowed the combination of the extreme forms on either side of the range (scrofa and wvittatus) into one species. This species is therefore characterized by significant levels of naturally occurring geographic/genetic variation, duly compounded by anthropogenic interferences through widespread releases (whether deliberate or accidental) of pure-bred, hybrid, and domesticated variants originating from other parts ofits wide range. An astonishingly large number of subspecies have therefore been proposed and recognized in the literature, some of which are clearly invalid. Precise analysis of the likely number of truly recognizable/differentiated subspecies is still a matter of debate and disagreement, given that 4-25 subspecies have been recognized by different authors. Of these, C. P. Groves undertook by far the most comprehensive review when proposing the recognition of at least 16 morphologically distinct populations of S. scrofa on the basis of external as well as craniometric characteristics. His work has since been challenged by P. Genov, who proposed recognition of only four subspecies based on similar craniometric analyses, but these analyses were flawed inasmuch as they did not include some of the most distinct populations of these animals. Nonetheless, Genov merged these subspecies into four broadly geographic groupings, thereby broadly mirroring Groves’s more comprehensive review. These were the WESTERN RACES or the “ scrofa group,” at least six, but possibly as many as eight subspecies (scrofa, meridionalis, baeticus, majori, algirus, attila, lybicus, and nigripes), but only two (algirus and meriodionalis) have clearly defined ranges; INDIAN RACES or “cristatus group,” three races (dauvidi, cristatus, and affinis), none with precisely defined ranges; EASTERN RACES or “leucomystax group,” possibly up to seven subspecies (sibiricus, ussuricus, coreanus, leucomystax, riukiuanus, tarvanus, and moupinensis), though only three (leucomystax, riukiuanus and taivanus) have clearly defined ranges; and a highly disctinctive SUNDAIC RACE (viltatus), though presumably genetically continuous with cristatus in the northern limits of its range in Indochina. We follow Groves’s taxonomy because of the strength and breadth of his analysis and his use of external characteristics that were not incorporated in Genov’s analysis. However, new (e.g. phylogenetic) data sets are most likely to strengthen the case for recognizing particular additional subspecies, or elevating some currently recognized subspecies to full species, or merging other, currently recognized subspecies. Groves has questioned whether his subspecies are all variants of one species or a complex of several different species, and has recently proposed the elevation of both vitattus and moupinensis subspecies to full species status. Of these, vittatus is more easily comprehensible, being morphologically and geographically distinguishable as the so-called “Indonesian Banded Pig,” occurring throughout the distal limits of S. scrofa’s range in South-east Asia, whereas S. moupinensis is apparently confined to Myanmar, Indochina, and south-eastern China (Fujian), and therefore also includes the problematic Indochinese Pig (S. bucculentus) from the Annamite Mountains. The taxonomic identity of S. bucculentus remains unclear. Since its description in 1892 by Heude, based on two skulls from Vietnam, only one skull of similar shape and size as the original two has been reported, from Laos. However, reexamination of the skull dimensions of the type specimens and phylogenetic studies suggest that S. bucculentus might not be a distinct species, but a geographically restricted variant of S. scrofa. The possibility that S. bucculentus might be a synonym of S. scrofa is supported by reports from local informants that do not mention facial warts. Warts would be expected if indeed S. bucculentus was more closely related to other South-east Asian warty pigs of the subgenus Euhys. Recent studies have made it more likely that S. bucculentus will be merged with a taxon closelyaffiliated to or part of S. scrofa. As if to complicate matters, Groves has also recently proposed recognition of two more species, namely S. chirodontus described by Heude in 1888 from south-central China (including Kienté, Ningkua, Zhejiang, Shaanxi, Anhui, and also Korea), and S. ussuricus described also by Heude in 1888 from Heilongjiang and far eastern China and Russia. Similarly sharp boundaries between various other mainland Asia subspecies do not exist, especially given evidence of hybridization between salient forms (e.g. davidi and cristatus). However, until these races are formally described and elevated, we retain the existing taxonomy for S. scrofa. We keep subspecies coreanus for now as it is distinct from wussuricus, but note that it was recently proposed for inclusion in moupinensis. Nineteen subspecies are recognized. Subspecies and Distribution. S. s. scrofa Linnaeus, 1758 — W Europe, from Denmark, Germany, Poland, and Czech Republic to N Italy and N Iberian Peninsula; possibly also Albania. The taxonomic status of animals in Austria, Switzerland, Slovenia, and Slovakia is unclear but presumably these populations are included in scrofa, as are the populations of Sweden, Finland, and the Baltic states. However, restocking of once depleted populations, for example in Italy, has likely involved the introduction and mixing of this subspecies with other subspecies, such as attila. S. s. affinis Gray, 1847 — S India and Sri Lanka. S. s. algirus Loche, 1867 — Tunisia, Algeria, and Morocco, on the coastal side of the mountains or in the low montane areas. S. s. attila Thomas, 1912 — Hungary, Ukraine, C & S Belarus, Romania, Moldova, and S Russia towards the N flank of the Caucasus, but not including the Transcaucasian countries of Georgia, Armenia, and Azerbaijan. The range possibly extends as far S as the Mesopotamian Delta in Iraq, in which case it would likely include W & SW Iran, and possibly E Turkey and Syria, where it borders with lybicus. Such a range could not be easily reconciled with a statement by Groves that “the difference between pigs from N and S of the Caucasus is quite striking; Transcaucasian boars are certainly not attila.” This subspecies may also extend into C Asia and include Kazakhstan, Uzbekistan, and Turkmenistan, but no data exist to support this. S. s. baeticus Thomas, 1912 — originally described from Coto Donana, S Spain, and later merged with meridionalis; also S Portugal. Unless evidence is found that these Italian and Iberian populations are the relics of a much larger formerly contiguous range, this subspecies should be kept as distinct. S. s. coreanus Heude, 1897 — Korean Peninsula. S. s. eristatus Wagner, 1839 — Himalayas S to C India and E to Indochina (N of the Kra Isthmus). S. s. davidi Groves, 1981 — the arid zone from E Iran to Gujarat, including Pakistan and NW India, and perhaps N to Tajikistan. S. s. leucomystax Temminck, 1842 — main Is ofJapan (Honshu, Shikoku, Kyushu, Nakadori, Hiburijima, Tojima, Kushima, and other smaller Is). S. s. lybicus Gray, 1868 — Bulgaria, Greece, Turkey, Syria, Jordan, Israel, Palestine, in the past also in Lybia, and Egypt. The former Yugoslavia was included in its range, which would suggest that now Slovenia, Serbia, Croatia, Bosnia and Herzegovina, Montenegro, and Kosovo are within the range of this subspecies, although the exact boundaries are unclear. Pigs from Albania have been assigned to S. s. scrofa. S. s. majori De Beaux & Festa, 1927 — C & S Italian Peninsula. S. s. menidionalis Forsyth Major, 1882 — Corsica and Sardinia, with the proviso that the two populations are very likely to be introduced or feral. S. s. moupinensis Milne-Edwards, 1871 — China, S to Vietnam and W to Sichuan. S. s. nigripes Blanford, 1875 — the flanks of the Tianshan mountains in Kyrgyzstan and NW China (Xinjiang). An animal photographed in NE Iran (Golestan) looked like this subspecies. S. s. nukiuanus Kuroda, 1924 — Iriomote, Ishigaki, Okinawa, Tokunoshima, Amamioshima, and Kakerome Is in the Ryukyu chain in extreme S Japan, though some of these populations have hybridized with introduced domesticates. S. s. sibiricus Staffe, 1922 — Mongolia and Transbaikal (S & E of Lake Baikal). S. s. tawvanus Swinhoe, 1863 — Taiwan. S. s. ussuricus Heude, 1888 — far E Russia and the Manchurian region (China). Korean populations were previously included in this subspecies, but based on new evidence, the Korean taxon seems more similar to moupinensis. S. s. vittatus Boie, 1828 — Malay Peninsula, S of the Isthmus of Kra, the offshore islands of Terutai and Langkawi, Sumatra, Riau Archipelago, Java, Bali, and a range of smaller islands around these, including Babi, Bakong, Batam, Bawean, Bengkalis, Bintan, Bulan, Bunguran, Cuyo, Deli, Durian, Enggano, Galang, Jambongan, Karimon (Riau Is), Kundur, Lagong, Laut, Lingga, Lingung, Mapor, Moro Kecil, North Pagai, Nias, Panaitan, Payong, Penang, Pinie, Rupat, Siantan, Siberut, Simeulue, Singkep, Sugi, Sugi Bawa, Telibon, Tinggi, Tuangku, and the Tambelan Is. This species was originally present from the British Is in the extreme W, through Eurasia from S Scandinavia to S Siberia, extending as far E as Korea and Japan, and SE into some of the Sunda Is and Taiwan. In the S the species ranged along the Nile Valley to Khartoum, and N of the Sahara in Africa, more orless following the continental coasts of S, E, and SE Asia. Within this range it was absent only from extremely dry deserts, e.g. the driest regions of Mongolia and in China W of Sichuan; and alpine zones, such as the high altitudes of Pamir and Tien Shan. In recent centuries, the range of S. scrofa has changed dramatically because of hunting and changes in available habitat. The species disappeared from the British Is in the 17" century, from Denmark in the 19" century, and was greatly reduced in range and numbers in the 20" century from areas as distant as Tunisia, Sudan, Germany, and Russia. Following these severe declines, there were some slight population recoveries in Russia, Italy, Spain, and Germany in the mid-20™ century, and natural and assisted range expansions in Denmark and Sweden. The species has also been inadvertently reintroduced in various locations in the Great Britain via escapees of mixed origin from commercial farming enterprises. Ex-S. scrofa stocks also occur as introduced feral populations in various other parts of the world, including Australia, New Zealand, the eastern Malay Archipelago, and in North, Central, and South America. In all of these areas they are now generally recognized as a major pest. Descriptive notes. Head-body 90-200 cm, tail 15-40 cm, shoulder height 55-110 cm; weight 44-320 kg. This is a moderate to large pig with a relatively short muzzle and no facial warts. The species is sexually dimorphic, with females about 80% the size of males. Size varies significantly between subspecies. Generally speaking, S. scrofa follows Bergmann’s Rule, with smaller animals nearer the tropics and larger, smaller-eared ones in the north ofits range. The coatis coarse and bristly, and varies in color from brown to almost black, usually turning grayish with age. There are great regional differences in color, and nearly white animals are known from central Asia. Several subspecies have dense underwool. The face, cheeks, and throat are slightly grizzled with whitish hairs, becoming distinctly white or forming white bands in some subspecies. The back is rounded and the legs are relatively long, especially in northern subspecies. Young are born generally brown with a pattern of longitudinal darker brown stripes, known aslivery, along their torso. This pattern fades between the second and sixth month, and the juveniles reach adult coloration at one year of age. The head is long and pointed, without an obvious beard, warts, or facial tufts. The upper canines form tusks that curve out and upwards. The lower canines are kept sharp by rubbing against the upper canines. These canines measure about 20 cm in adult males, and in exceptional cases even 30 cm. In females they are smaller. There is significant geographic variation in S. scrofa. WesTERN RACES: The nominate subspecies scrofa has an adult male skull length between 36-3 cm and 40-6 cm, which further increases towards the border ofits range with the subspecies attila. The species is dull to dark brown or olive-gray, with copious dark-gray or red-brown underwool, and a noticeable mane, which is often long and thick. Bodyweight in scrofa varies significantly from 54 kg to over 200 kg in males, with sows being quite a bit smaller (44-6-61-4 kg). Towards Spain and Italy body size decreases gradually. In northern Spain, the mean body weight of 637 mature males and females was 74-3 kg and 55-3 kg, respectively. The mean head and body lengths of males and females were 154-4 cm and 142-2 cm, respectively. The subspecies baeticus in southern Spain and meridionalis in the islands of Sardinia and Corsica are significantly smaller than scrofa, with mean skull lengths for males between 30-8 cm and 32-7 cm. These similar looking subspecies are colored a dull olive-fawn, with sparse underwool, and mostly lacking a mane. There is obvious clinal variation from north-western Europe to southern Spain, and it is unclear where the boundary between subspecies scrofa and baeticus is. In central and southern Italy, the subspecies major: is apparently smaller than scrofa, with a higher and wider skull. Since the 1950s, it has hybridized extensively with introduced scrofa populations, which likely obscures morphological differences. Farther south, in northern Africa, the subspecies algirus is like scrofa but has smaller teeth and a broader occiput. The coat of this subspecies is black with yellowish or reddish tips, dark brown underwool, and not much of a mane. Subspecies attila is very large, with skull length in males over 45 cm. It has relatively small teeth, but M,is long, always over 4 cm. Subspecies attilais usually pale yellow-gray, with hair tips long and straw-yellow, copious brown underwool, and a long mane that extends to the loins. Recent information suggests that the subspecies is less distinct than previously thought and might overlap in size as well as chromosomal arrangement with scrofa. Subspecies lybicus is small, pale and almost maneless. Subspecies nigripes is a pale-colored subspecies with dark legs, which are usually paler behind, a nearly white face, and no mane. It has a very broad skull. Weights of male wild pigs from present-day Uzbekistan and southern Kazakhstan are given as 220-240 kg. Like subspecies scrofa, race nigripes has 36 chromosomes, not the 38 that are usual for the species, but the translocation is different. EASTERN RACES: sibiricus is a fairly small pig with a relatively short face (short nasals and palate) compared to similar sized pigs. It has a very high skull with broad occiput. It also stands out for the shape ofits lacrimal bone (as measured by the proportion between suture height of the lacrimal bone at the orbit and its lower suture length), which is 1-0 for males (n = 7) and 0-87 for females (n = 4). Subspecies ussuricus is the largest of S. scrofa, with male wild pigs often weighing over 300 kg. It has a low-crowned skull and thick pelage, which is yellowish-gray in winter and black in summer when the long, pale hair tips have worn off. Subspecies ussuricus has black legs, sharply paler on the posterior surfaces. The face is black and has a clear mouth-gonion band. Initially, pigs from the Korean Peninsula had been included in race ussuricus, but their small size and genetic as well as morphological similarity to race moupinensis makes that affinity less likely. We presently retain this as a distinct subspecies coreanus, but recognize that it might well be included in moupinenss. Subspecies leucomystax is a smallish, short-legged, yellow-brown pig, with virtually no mane. There is a neat cline of diminishing size from north to south, but this apparently doesn’t warrant further division of this subspecies. The island race riukiuanus is by far the smallest subspecies. On the basis of a small data set, there appears to be no sexual size difference; three males with third molars in wear averaged 26-3 cm, and three females 26-1 cm in “profile length,” which presumably equals greatest skull length. Recent phylogenetic studies have shown that this subspecies is more closely related to the mainland China form than to leucomystax from the main islands ofJapan. This is also confirmed by studies of crania and mandibles, which are quite distinct from leucomystax. Subspecies riukiuanus is a prime candidate to be recognized as a full species. Race taivanus from Taiwan is a small black pig with markings on the side of the snout, as judged from camera trap pictures. Measurements of mandibles show considerable overlap between taivanus and leucomystax, but with riukiuanus being quite distinct. The occiput in taivanus is shorter than in leucomystax, with little overhang. Subspecies moupinensis is a fairly small, yellowish (in south of range) or darker (in north), short-maned pig with a broad, high-crowned skull, from most of China and Vietnam. Elevation to full species status was recently proposed for this taxon. SOUTH ASIAN RACES: The subspecies of India, Burma, and western Thailand, cristatus is long-maned, with a coat thatis brindled black, unlike race david: (see below). Subspecies cristatus is more lightly built than European subspecies, and it has a larger and more pointed head, and smaller and more pointed ears. The plane of the forehead is straight, whereas it is concave in the European subspecies. Subspecies cristatus differs little from moupinensis, but has a much longer mane, which extends to the rump. Itis darker than moupinensis. Race davidi is a small, light brown pig, with a long thick mane, and without any black on the legs. Weights of wild pigs from Tajikistan, which might be this subspecies, were reported as 74-144 kg, and occasionally up to 158 kg for males, and 71-123 kg for females. This subspecies belongs to the low-crowned pigs of the western part of S. scrofa’ distribution range, rather than to the eastern pigs of India, China, and the rest of east and South-east Asia. Race affinis of southern India and Sri Lankais larger than cristatus, overall black or occasionally dark brown. MALAYAN RACE: Sometimes referred to as the Indonesian Banded Pig, of peninsular Malaysia and western Indonesia is a small, lowcrowned, short-faced pig with very sparse pelage. It is generally brown or agouti colored, with black legs, and typically has a distinct whitish band extending from either side of the snout to the jowls (hence & : Published as part of Don E. Wilson & Russell A. Mittermeier, 2011, Suidae, pp. 248-291 in Handbook of the Mammals of the World – Volume 2 Hoofed Mammals, Barcelona :Lynx Edicions on pages 288-290, DOI: 10.5281/zenodo.5721014